Discourse markers in early Koine Greek: cognitive-functional analysis and LXX translation technique - Fresch, Christopher J. (Septuagint and cognate studies, 2023)
"Using a cognitive-functional linguistic framework and cross-linguistic research on discourse markers, Christopher J. Fresch investigates the use of five discourse markers in the early Koine Greek found in the documentary papyri of the third to first centuries BCE and the Greek translations of the Hebrew Bible. Through this analysis, Fresch proposes linguistically grounded descriptions for how each discourse marker guides readers in how they process and comprehend the text. Based on these descriptions, he examines the instances of these discourse markers in the Minor Prophets and how the translator used them to render the Hebrew text. Fresch presents a picture of a translator who selected discourse markers based on their own understanding of the structure, flow, and meaning of the underlying Hebrew text. Their use attests to a translator who was contextually aware and who desired to produce a translation in idiomatic Koine" --